Employment outcomes in the welfare state - Ngai, L. Rachel; Pissarides, Christopher A. (London, 2008)
"We examine the implications of tax and subsidy policies for employment in the "three worlds of welfare", Anglo-Saxon, Continental European and Scandinavian. We argue that home production is key to a proper evaluation of the employment outcomes. Anglo-Saxon low-support policies encourage more overall market employment. Continental transfer polilcies encourage more home production in services with close substitutes at home. Scandinavian policies give incentives to move home production in social services to the market but discourage other service activity. We find support for our claims in sectoral employment data for five representative countries, United States, Britain, France, Italy and Sweden."